PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS ALUMNI MELALUI KEPUASAN PELANGGAN DAN PROMOSI SEBAGAI VARIABEL MODERASI DI SMP NEGERI 3 KALORAN KABUPATEN TEMANGGUNG - Eva Indrayani; Agus Wahyudin; Joko Sutarto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education plays important role in improving the quality of human resources and maintaining its existence, alumni loyalty is a major factor in maintaining a school’s reputation, but many alumni lose their emotional attachment to the school after graduating. This study analysis the effect of service quality on alumni loyalty through customer satisfaction with promotion as a moderating variable at SMP Negeri 3 Kaloran. This study uses a quantitative method with a survey method. Data were collected through questionaires to 128 alumni selected using the proportional statified random sampling technique. Data analysis using IBM SPSS version 25. The results showed that service quality had a positive effect on laumni loyalty and customer satisfaction, while customer satisfaction did not have a significant effect on alumni loyalty. Customer satisfaction did not act as asignificant mediating variable in the relationship between service quality and alumni loyalty. And promotion has been shown to strenghten the relationship between customer satisfaction and alumni loyalty. This study recommends improving service quality, techer communication with alumni, and strengthening digital promotions to strenghten alumni relationship with school.